Armoured brain due to chronic subdural collections masking underlying hydrocephalus. (August 2013) - Salunke, P.; Aggarwal, A.; Madhivanan, K.; Futane, S.
Abstract: Calcified chronic subdural collection (armoured brain) is a known long-standing complication of shunt overdrainage. We report a young male who became symptomatic eleven years after a shunt surgery. Radiology showed bilateral calcified subdural collections. Drainage of these collections did not help, but shunt revision did. Patients with armoured brain syndrome who suddenly become symptomatic should possibly undergo shunt revision before the more extensive and morbid procedure of drilling the membranes.